2019
DOI: 10.4236/jdm.2019.94017
|View full text |Cite
|
Sign up to set email alerts
|

The Level and Role of Interleukin-17 in Patients of Type 2 Diabetes Mellitus with and without Complications

Abstract: Background: Type 2 Diabetes Mellitus (T2DM) is the most prevalent metabolic disorder in the world. Recent evidence however suggests that T2DM is not only a disease of metabolism, but also an inflammatory disorder and that inflammation also plays an important role in the pathogenesis of Diabetic complications. Our aim was to study the level of interleukin-17 (IL 17) in Indian populations with T2DM as an inflammatory marker and analyze its role in different diabetic complications. Methods: A total of consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…We observed a significant increase in the concentration of (FBG) in group (DF) and (DN) compared to group (DM) (P≤0.05). This result is consistent with the results of the study (37) .…”
Section: Fasting Blood Glucose Concentration: Tablesupporting
confidence: 94%
See 1 more Smart Citation
“…We observed a significant increase in the concentration of (FBG) in group (DF) and (DN) compared to group (DM) (P≤0.05). This result is consistent with the results of the study (37) .…”
Section: Fasting Blood Glucose Concentration: Tablesupporting
confidence: 94%
“…Self-management (controlling the fasting blood sugar level) of diabetes is an essential element to prevent or mitigate complications of diabetes, as (40) it was stated that (FBG) levels increased in diabetic foot patients compared to diabetic patients, because the chronic elevation (FBG) leads to diabetic neuropathy. Which is the gateway to diabetic foot syndrome, as revealed in this study (37) . There is a positive correlation between IL-6 and FBG levels in each of DF(r = 0.29), DN (r= 0.33) and DM (r = 0.21) as shown in figure (1).…”
Section: Fasting Blood Glucose Concentration: Tablementioning
confidence: 59%
“…Our data suggests that the inflammatory milieu in GK rats is most likely due to T c 17 cells and activated monocytes, NK cells as represented by elevated CD161a+ cells. In the human context, T2D patients have been shown to have higher IL-17 levels compared to healthy controls, which contribute to the pro-inflammatory phenotype commonly observed in T2D ( 64 , 65 ), thereby justifying our hypothesis.…”
Section: Discussionmentioning
confidence: 53%
“…(Galil et al 2015) found that mean serum levels of IL-17 in SLE patients were significantly higher (19.54 pg/ml) at (p < 0.001) in relation to Healthy control group( 10.78 pg/ml)and observed that patients with LN had lower levels of IL-17 during periods of remission with mean (13.18 pg/ml) than in active disease. Parhi et al,(2019) reported that the levels of IL 17 (normal level ≤ 10 pg/ml) was found to be increased in DM (mean = 25.06 pg/ml) which is higher than in non-diabetic controls (mean = 5.232 ± 2.867 pg/ml) . Kuen et al .,(2020) noted that Th17 frequency is higher in the tumor cell than in healthy tissues or PBMCs,tumor cells and demonstrated elevated IL-17 production associated with persistence inflammation.…”
Section: Il-17 Concentration In Hemodialysis Patients According To Ca...mentioning
confidence: 91%
“…Figure 4: Illustrate IL-17 serum level in hemodialysis patients according to cause of disease Radwanetal.,(2021)show that serum levels of IL-17 were significantly higher among patients with SLE as compared to healthy controls with a median 138 pg/nl versus 8.6 pg/nl respectively (p=0.001). (Galil et al 2015) found that mean serum levels of IL-17 in SLE patients were significantly higher (19.54 pg/ml) at (p < 0.001) in relation to Healthy control group( 10.78 pg/ml)and observed that patients with LN had lower levels of IL-17 during periods of remission with mean (13.18 pg/ml) than in active disease Parhi et al,(2019). reported that the levels of IL 17 (normal level ≤ 10 pg/ml) was found to be increased in DM (mean = 25.06 pg/ml) which is higher than in non-diabetic controls (mean = 5.232 ± 2.867 pg/ml) Kuen et al .,(2020).…”
mentioning
confidence: 97%